’Double Trouble’ - management of iridodialysis and subluxated cataract in an eye with blunt injury - Srirampur, Arjun; Manwani, Sunny; Amula, Gangaprasad; Andru, Pavani Reddy (International Surgery Journal, 2017)
The aim of this study was to report a case of iridodialysis repair along with cataract extraction and iris claw lens implantation in a case of superior iridodialysis with subluxated cataractous lens following a blunt ocular trauma.